Le décor peint du refuge de l’abbaye augustine du Mont Saint Éloi à Arras (fin XVe-début XVIe siècle) - Laurence Baudoux-Rousseau; Hugues Dewerdt; Matthieu Fontaine (In Situ)
The Wetz d’Amain is the only medieval building standing in Arras. It was erected in the 1450s, as a place of refuge during the war years for the friars of Mont-Saint-Éloi, an augustinian abbey about 10 km from the town. Unoccupied for a very long time, it is in bad repair and deteriorates. In the 1980s, mural paintings were discovered in the upper room, the greatest of the building: four medallions (tondo) surrounded with foliage, the subject of which seemed mysterious: - two men wearing a helmet, with arm in the hand, - a man who squeezes a sponge, - another one on a throne, in an assembly, - a donkey with a packsaddle, grazing on. Each of these scenes is completed with a short but partly obliterated text. Today, we know the scenes depict some of the Alciato’s Emblemata, in the 1615 edition. And the inscriptions have something to do with money. The using of the room is unknown (the archives have disappeared) and this choice remains unexplained.